2020
DOI: 10.1051/0004-6361/202038250
|View full text |Cite
|
Sign up to set email alerts
|

The Sun at millimeter wavelengths

Abstract: Context. Solar observations with the Atacama Large Millimeter/sub-millimeter Array (ALMA) facilitate studies of the atmosphere of the Sun at chromospheric heights at high spatial and temporal resolution at millimeter wavelengths. Aims. ALMA intensity data at millimeter(mm)-wavelengths are used for a first detailed systematic assessment of the occurrence and properties of small-scale dynamical features in the quiet Sun. Methods. We analyzed ALMA Band 3 data (∼3 mm/100 GHz) with a spatial resolution of ∼1.4–2.1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 42 publications
7
37
2
Order By: Relevance
“…The local minimum with the highest temperature (here the post-shock minimum) is referred to as the ‘base temperature‘. The time between the two local minima is 146 s. Estimating the lifetime of the observable brightness temperature signature as the Full Width Half Maximum (FWHM) of the peak results in t FWHM = 41 s. The brightness temperature excess and lifetime shown here are in line with values derived from shock wave propagation in 1D simulations [13,14,43]. The resulting strong correlation between the gas temperature at z ( τ = 1.0) and the brightness temperature (figure 4 b ) is expected for mm-wavelength radiation (i.e.…”
Section: Example Of Shock Wavesupporting
confidence: 80%
“…The local minimum with the highest temperature (here the post-shock minimum) is referred to as the ‘base temperature‘. The time between the two local minima is 146 s. Estimating the lifetime of the observable brightness temperature signature as the Full Width Half Maximum (FWHM) of the peak results in t FWHM = 41 s. The brightness temperature excess and lifetime shown here are in line with values derived from shock wave propagation in 1D simulations [13,14,43]. The resulting strong correlation between the gas temperature at z ( τ = 1.0) and the brightness temperature (figure 4 b ) is expected for mm-wavelength radiation (i.e.…”
Section: Example Of Shock Wavesupporting
confidence: 80%
“…Recent studies have shown the potential of ALMA to examine distinct phenomena both in quiet and active regions [3140]. In particular, Eklund et al [41] found signatures of shock-wave events in Band 3 (2.8–3.3 mm) observations from December 2016, coming to the conclusion that there are numerous small-scale dynamic structures with lifetimes of 43–360 s present in the ALMA field of view (FOV), with excess temperatures of more than 400 K and a correlation between their occurrence and the magnetic field strength. Characterization of such events at millimetre wavelengths has also been studied in detail from numerical simulations [42].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the technical challenges, an increasing number of studies based on ALMA observations of the Sun is being published (see, e.g. Bastian et al 2017;Shimojo et al 2017b;Yokoyama et al 2018;Brajša et al 2018;Jafarzadeh et al 2019;Rodger et al 2019;Selhorst et al 2019;Wedemeyer et al 2020;da Silva Santos et al 2020b;Eklund et al 2020;Nindos et al 2020;Patsourakos et al 2020;Brajša et al 2021;Chintzoglou et al 2021a;Guevara Gómez et al 2021;Jafarzadeh et al 2021;Nindos et al 2021;Eklund et al 2021a, and more). While scientific production using ALMA solar data is clearly picking up, interferometric imaging into stabilised, time-consistent data series in absolute temperature units remained difficult.…”
Section: Introductionmentioning
confidence: 99%